Gradients of the Intergenerational Transmission of Health in Developing Countries - Bhalotra, Sonia; Rawlings, Samantha (The Review of Economics and Statistics, 2013)
Abstract This paper investigates the sensitivity of the intergenerational transmission of health to changes in the socioeconomic and public health environment into which children are born using individual survey data on 2.24 million children born to 600,000 mothers during the period 1970 to 2000 in 38 developing countries merged by country and cohort with macroeconomic data. We find that children are more likely to bear the penalty exerted by poor maternal health if they are conceived or born in adverse socioeconomic conditions. Equivalently, shocks to the child's birth environment are more damaging of children born to women with weaker health at birth.